Impact of carbofurans on sweet corn pest predators: A study of good agroecosystem practices - Sapto Priyadi; Lutfi Ali Setiawan; Dwi Susilo Utami; Achmad Fatchul Aziez; R. Soelistijono; Haryuni (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2022)
Sweet corn (Zea mays var. Saccharata, Sturt) is a horticultural crop with high economic value. Sweet corn plants are susceptible to attack by plant pest organisms, reducing production yields. Using synthetic chemical pesticides of the carbamate group can reduce the diversity of predatory insects as biological controllers. Many farmers do not know about the role of predatory insects in agriculture, so there is often a mistarget in control. This study aimed to determine the diversity of predatory insects on sweet corn. The research was conducted in Cabeyan, Sukoharjo district, using the descriptive observation method. Data collection is done directly. In this study, several types of predatory insects were found, including three species from the Araneae order, two from the Odonata, one from the Hymenoptera, one from the Diptera, and one species from the Coleoptera.